Evolution Education Around the Globe (Springer International Publishing, 2018)
This edited book provides a global view on evolution education. It describes the state of evolution education in different countries that are representative of geographical regions around the globe such as Eastern Europe, Western Europe, North Africa, South Africa, North America, South America,Middle East, Far East, South East Asia, Australia, and New Zealand.Studies in evolution education literature can be divided into three main categories: (a) understanding the interrelationships among cognitive, affective, epistemological, and religious factors that are related to peoples' views about evolution, (b) designing, implementing, evaluating evolution education curriculum that reflects contemporary evolution understanding, and (c) reducing antievolutionary attitudes. This volume systematically summarizes the evolution education literature across these three categories for each country or geographical region. The individual chapters thus include common elements that facilitate a cross-cultural meta-analysis. Written for a primarily academic audience, this book provides a much-needed common background for future evolution education research across the globe. .